PEMODELAN UML SISTEM INFORMASI MONITORING PENJUALAN DAN STOK BARANG (STUDI KASUS: DISTRO ZHEZHA PONTIANAK) - Ade Hendini (Universitas Bina Sarana Informatika, 2016)
In the business world, technology can be used as a tool to monitor the activities going on in the business including sales transaction and monitoring stock of merchandise available. This is done in an effort to determine the progress of a business. In design information systems monitoring sales and inventory used UML modeling to analyze what is needed and what will be built. Monitoring information system sales and inventory is expected to be a tool that can help businesses to be able to know the progress of his efforts in each branch.Keyword: UML, Monitoring, Modeling